Vitamin K deficiency: a case report and review of current guidelines - Maria Rosaria Marchili; Elisa Santoro; Alessandra Marchesi; Simona Bianchi; Lelia Rotondi Aufiero; Alberto Villani (BMC, 2018)
Abstract Background Vitamin K, a fat soluble vitamin, is a necessary cofactor for the activation of coagulation factors II, VII, IX, X, and protein C and S. In neonatal period, vitamin K deficiency may lead to Vitamin K Deficiency Bleeding (VKDB). Case presentation We present the case of a 2 months and 20 days Caucasian male, presented for bleeding from the injections sites of vaccines. At birth oral vitamin K prophylaxis was administered. Neonatal period was normal. He was exclusively breastfed and received a daily oral supplementation with 25 μg of vitamin K. A late onset vitamin K deficiency bleeding was suspected. Intravenous Vitamin K was administered with complete recovery. Conclusions Nevertheless the oral prophylaxis, our case developed a VKDB: it is necessary to revise the current guidelines in order to standardize timing and dosage in different clinical conditions.